Effects of fire intensity on soil microbial diversity and nitrogen cycling functional genes in forests (Northeast China) - Jia, Wenjie; Shu, Yang; Zhao, Pengwu; Zhou, Mei; Yue, Yongjie (Frontiers in Microbiology, 2025)
IntroductionForest fire disturbance is one of the most critical factors affecting forest ecosystems in Northeast China. It disrupts ecosystem balance, alters soil physical and chemical properties, and significantly impacts soil microbial communities and nitrogen cycling. Understanding these changes is essential for post-fire vegetation restoration and nitrogen pool reconstruction.MethodsThis study focused on a burned Larix gmelinii forest in the Daxing’an Mountains. We investigated soil environmental factors, microbial community structure, nitrogen cycle genes, and their interrelationships under different fire intensity conditions.Results(1) Light fire increased soil pH, total nitrogen (TN), soil organic carbon (SOC), nitrate nitrogen (NO3–-N), and available phosphorus (AP), but reduced soil moisture content (SMC), microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), and ammonium nitrogen (NH4+-N). Severe fire raised bulk density (BD), available potassium (AK), AP, and NO3–-N, while decreasing SMC, MBC, MBN, NH4+-N, and TN. (2) Bacterial diversity (Shannon index) increased after light fire but decreased after severe fire; richness indices (Sobs and Chao1) declined under both fire conditions. Fungal diversity and richness declined with both light and severe fires. Dominant soil bacterial phylum was Proteobacteria (with Bradyrhizobium as dominant genus), while dominant fungal phylum was Basidiomycota (with Russula as dominant genus). (3) Abundance of nitrogen fixation gene nifH declined with increasing fire intensity. Abundance of nitrification genes amoA-AOA and amoA-AOB significantly increased. Denitrification genes (nirK, nirS, nosZ) increased after light fire but decreased after severe fire. (4) Soil nitrogen (MBN, TN, NH4+-N, NO3–-N) had a direct positive effect on nitrogen cycle genes, while fire intensity, available nutrients (AP, AK), and bacterial communities had direct negative effects.DiscussionThe findings reveal the complex response of soil properties, microbial communities and nitrogen cycle genes to different fire intensities. These findings provide a scientific basis for effective post-fire ecosystem management and soil fertility restoration in the boreal forest.